Breeding Plantation Tree Crops: Temperate Species - Jain, Shri Mohan; Priyadarshan, P.M (Springer New York : Imprint: Springer, 2009)
Tree species, spread across a wide range of genera, are indispensible to human life. Their breeding, poised to satisfy human needs, presents significant challenges. Tree crops face a variety of agronomic and horticultural problems in propagation, yield, appearance, quality, diseases and pest control, abiotic stresses and poor shelf-life. Additionally, shrinkage of cultivable land and the pressure of growing demand have resulted in growth of tree crops under marginal conditions that call for concerted efforts for their genetic improvement. Increased attention to the environment, sustainability and diet in recent years in turn magnifies the importance of study of these crops. With the use of modern molecular and biotechnological tools, the task of improving yield in tree crops is foremost in the acumen of future global agricultural research for sustainable production. This 2-volume book series deals with both tropical and temperate tree crop species, and represents an effort toward compilation of all available worldwide research on these subjects. This volume covers the following temperate species: almond, apple, apricot, citrus, pear, plum, raspberry and walnut. The contributing authors are internationally-known specialists who provide first hand comprehensive knowledge. All contributory book chapters have been peer reviewed and revised accordingly. This book series is an indispensable reference for scientists, researchers, teachers, students, policy makers and planters. S. Mohan Jain, Plant Biotechnologist, University of Helsinki, Helsinki, Finland P. M. Priyadarshan, Plant Breeder, Rubber Research Institute of India.